Social Segregation as a Determinant of Urban Development: Gated Communities and Self-Segregation in San José and Heredia, Costa Rica - Pujol M., Rosendo (2011)
This article provides a quantitative description of gated communities concentration patterns in the cities of San Jose and Heredia, Costa Rica (for 2007), by estimating Moran’s I globally and locally, using a LISa. The cities were also analyzed in terms of residential segretagion; for each district, indexes of equality, exposition, and concentration – including corrections by area, shape and frontier of census tracts composing each unit analyzed – for high and low income groups. These indexes, in conjunction with additional covariates (deaths by murder rates, income and accessibility to San Jose), were used to evaluate their influence as determinants of gated communities location. Models were estimated using Geographically Weighted Regressions to reflect spatial variability of parameters and statistical significance. This analysis seeks to prove the strong influence of residential segregation patternso on gated communities location in San Jose and Heredia